Measurement of tensor analyzing powers in deuteron photodisintegration; Physical Review Letters; Vol. 98, № 18 - Rachek I. A.; Barkov L. M.; Belostotsky S. L.; Dmitriev V. F.; Dyug M. V.; Gilman R.; Holt R. L.; Lazarenko B. A.; Mishnev S. I.; Nelyubin V. V.; Nikolenko D. M.; Osipov A. V.; et al. (2007, 2007)
New accurate measurement of tensor analyzing powers T20, T21 and T22 in deuteron photodisintegration has been performed. Wide-aperture non-magnetic detectors allowed to cover broad kinematic ranges in a single setup: photon energy = 25 to 600 MeV, proton emission angle in CM = 24 to 48 deg. and 70 to 102 deg. New data provide a significant improvement of a few existing measurements. The angular dependency of the tensor asymmetries in deuteron photodisintegration is extracted for the first time